Visualisasi Makna Lagu “Gala Bunga Matahari” Karya Sal Priadi dalam Fotografi Ekspresi - Adesa, Ismi; Emas, Cindi Adelia Putri (TSAQOFAH, 2025)
This creative final project was driven by the desire to translate the emotional depth and profound message of Gala Bunga Matahari, a song by Sal Priadi, into visual form through expressive photography. The song was chosen for its poetic lyricism, rich in symbolism, personal emotion, and inner narratives of loss, longing, and hope. The main objective of the project is to represent the emotional journey conveyed in the song through visual works that are both evocative and reflective. The creation process employed a qualitative approach using the phenomenological method, emphasizing the artist's subjective experience in responding to the song’s meaning. Charles S. Peirce’s semiotic theory served as the analytical foundation, focusing on three core elements: representamen, object, and interpretant, with the sunflower serving as the central symbol. Visual elements such as light, shadow, color, and composition were carefully selected to express emotions that are difficult to articulate verbally. Expressive photography was chosen as the medium due to its ability to convey emotion visually without relying on textual narration. The final work consists of 20 photographs printed on matte-laminated photo paper, functioning not only as a visual interpretation of the song but also as a medium for personal reflection and emotional healing for the creator. This project aspires to open new avenues for appreciating the intersection of music and photography as complementary forms of emotional communication.